PARTISIPASI MASYARAKAT DALAM PENGELOLAAN HUTAN ADAT DI DUSUN SUNGAI UTIK DESA BATU LINTANG KECAMATAN EMBALOH HULU KABUPATEN KAPUAS HULU - Liani, Meita Four; Roslinda, Emi; Muin, Sudirman (Universitas Tanjungpura, 2016)
Forest Sungai Utik subvillage is the first indigenous forest which receives ecolabel certification in Indonesia by sustainable forest management where this certification demonstrates the ability of communities in sustainable forest management. This study aims to determine the level of communities participation in the management of indigenous forest in Sungai Utik and analyze the impact of perception, age, education level, income level, long lived and the degree of dependence on the forest through the participation of indigenous communities in forest management in Sungai Utik subvillage. This research conducted by survey method, sampling is done by census respondents. Data ware taken for this study consisted of primary data and secondary data while the data analysis was done by descriptive and inferential (Linear Regression). The result of this study indicates that the participation of indigenous communities in forest management tend to be high, compared with the Arnstein theory community participation at the level of delegation of powers. There is a significant and positive impact that the level of income, level of perception and dependence of forest, whereas some which do not affect are level, age, education and length of stay. Key Word : Participation, management, indigenous forest